Durkheim, Bataille, and Girard on the Ambiguity of the Sacred: Reconsidering Saints and Demoniacs - Heinämäki, Elisa (Journal of the American Academy of Religion, 2015)
Why was it often difficult, in the late medieval religious world, to draw the line between saints and demoniacs? This article argues that the question—which goes to the core of the social construction of religious meaning—can be clarified by the notion of the sacred and in particular through the discussion on the ambiguity of the sacred as developed by Émile Durkheim, Georges Bataille, and René Girard. I further argue that the sacred must be understood not only as a symbolic but also as an affective and experiential reality. The saint and the demoniac can be seen as personifications of the sacred: set apart as exemplary incarnations of shared values but also objects of collective affects. The unstable position of holy persons is based on the ambivalence of the collective affect and its channeling in collective (ritual) practices.